Cities, Slums, and Early Child Growth : Empirical Evidence from Bangladesh - Raju, Dhushyanth; Kim, Kyoung Yang; Nguyen, Quynh T.; Govindaraj, Ramesh (World Bank, Washington, DC, 2017)
This study uses novel household survey data that are representative of Bangladesh's large cities, and of slum and nonslum areas within the cities, to investigate the effects of demographic and socioeconomic factors on early child growth in 2013. The study also decomposes the difference in mean child growth between slum and nonslum areas in 2013, and the increase in mean child growth in slum and nonslum areas from 2006 to 2013. Mother's education attainment and household wealth largely explain the cross-sectional difference and intertemporal change in child growth. Although positive in some cases, the effects of maternal and child health services, and potential health-protective household amenities, differ by the type of health facility, household amenity, and urban area. The results suggest that a focus on nutrition-sensitive programs for slum residents and the urban poor is appropriate.